Rozmyta wielokryterialna metoda porządkowania liniowego obiektów - Łuczak, Aleksandra; Wysocki, Feliks (Fuzzy multi-criteria method of linear ordering of objects, 2006)
The aim of this paper was to investigate the applicability of the fuzzy multicriteria linear ordering method to the construction of synthetic characteristics. Proposed approach base on two methods: analytical hierarchy process (to calculate weight of criterias) and method TOPSIST (to ranking of objects). The proposed procedure was employed to assess the socio-economic development of rural Wielkopolska seen as a collection of counties.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 148-158